Pengaruh Kinerja Keuangan Terhadap Financial Distress (Studi pada Perusahaan Asuransi yang Terdaftar di BEI Periode 2017-2021) - Ayu Gita Permata; Aminah (Jurnal EMT KITA, 2023)
The purpose of this study is to analyze the impact of profitability, solvency, and liquidity on the financial condition of 13 Indonesian Stock Exchange (IDX) listed insurance companies in the period 2017-2021. The sampling method used was direct sampling and data were analyzed using descriptive analysis, review, and hypothesis testing. We found that profitability (ROA), solvency (DAR) and liquidity (CR) have partially or simultaneously had a positive and significant impact on the degree of financial deterioration of insurers. These insights have a significant impact on the financial management of insurers and aid decision-making by industry managers, investors, and regulators. The results of this analysis could lead to a better understanding of the factors that influence financial hardship and encourage insurers to pay more attention to financial performance and better manage risk. This research can also make a valuable contribution to financial literature and can form the basis for further research on risk management and corporate finance in insurance and other areas of finance.